Immunization with BLS-Stx2B chimera totally protects dams from early pregnancy loss induced by Shiga toxin type 2 (Stx2) and confers anti-Stx2 immunity to the offspring - Sacerdoti, Flavia (2016)
Shiga toxin producing Escherichia coli (STEC) are bacterial pathogens involved in food-borne diseases. Shiga toxin (Stx) is the main virulence factor of STEC and is responsible for systemic complications including Hemolytic Uremic Syndrome (HUS). It has been previously demonstrated that Shiga toxin type 2 (Stx2) induces pregnancy loss in rats in early stage of pregnancy. The main purpose of this study was to determine if an active immunization prevents Stx2 mediated pregnancy loss and confers passive protective immunity to the offspring. For that purpose Sprague Dawley female rats were immunized with the chimera based on the enzyme lumazine synthase from Brucella spp. (BLS) and the B subunit of Shiga toxin 2 (Stx2B) named BLS-Stx2B. After immunization females were mated with males. At day 8 of gestation, dams were challenged intraperitoneally with a sublethal and abortifacient dose of Stx2. The immunization induced high anti-Stx2B-specific antibody titers in sera and most important, prevented pregnancy loss. Pups born and breastfeed by immunized dams had high anti-Stx2B-specific antibody titers in sera. Cross-fostering experiments indicated that passive protective immunity against Stx2 was transmitted through lactation. These results indicate that immunization of adult female rats with BLS-Stx2B prevents Stx2-induced pregnancy loss and confers anti Stx2 protective immunity to the offspring.